2018
DOI: 10.1029/2017ja025068
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Global Martian Plasma Models in the Context of MAVEN Observations

Abstract: Global models of the interaction of the solar wind with the Martian upper atmosphere have proved to be valuable tools for investigating both the escape to space of the Martian atmosphere and the physical processes controlling this complex interaction. The many models currently in use employ different physical assumptions, but it can be difficult to directly compare the effectiveness of the models since they are rarely run for the same input conditions. Here we present the results of a model comparison activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

5
3

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 68 publications
1
18
0
Order By: Relevance
“…Boesswetter et al () and Simon et al () made similar arguments regarding the asymmetry of the ICB, and showed hybrid simulation results consistent with these expectations. Other Mars plasma simulations with appropriate physics included (for instance, hybrid and multifluid MHD models) typically display similar features (Brecht & Ledvina, ; Dong et al, ; Modolo et al, , ; Najib et al, ), albeit with differences in the details, as expected given the differences in implementation of the various models (Brain et al, ; Egan et al, ). One of our primary purposes in this study is to determine whether MAVEN observations can confirm or disprove these expected asymmetries.…”
Section: Introductionmentioning
confidence: 74%
“…Boesswetter et al () and Simon et al () made similar arguments regarding the asymmetry of the ICB, and showed hybrid simulation results consistent with these expectations. Other Mars plasma simulations with appropriate physics included (for instance, hybrid and multifluid MHD models) typically display similar features (Brecht & Ledvina, ; Dong et al, ; Modolo et al, , ; Najib et al, ), albeit with differences in the details, as expected given the differences in implementation of the various models (Brain et al, ; Egan et al, ). One of our primary purposes in this study is to determine whether MAVEN observations can confirm or disprove these expected asymmetries.…”
Section: Introductionmentioning
confidence: 74%
“…Here we describe some of the general differences and motivate our selection of parameters. Our initial base case (R0), is the same as that studied by Egan et al (2018), and is an example of a typical solar wind experienced by Mars. The final case (R4), is identical to the case considered for Trappist-g by Dong et al (2018), where the stellar wind was reconstructed using the Alfven Wave Solar Model (van der Holst et al 2014).…”
Section: Stellar Parametersmentioning
confidence: 99%
“…Instead, the spatial location of the plume may vary with time, in response to either variations in upstream parameters or local dynamics. Most simulations predict that the plume has a relatively narrow structure (Egan et al, ). If a narrow dense plume moved back and forth across the orbit plane (i.e., a “flapping” motion), it could lead to signatures like those observed.…”
Section: Observations Of Boundary Layer Structure and Instabilitiesmentioning
confidence: 99%